Robust MPC for actuator-fault tolerance using set-based passive fault detection and active fault isolation - Xu, Feng; Puig, Vicenç; Ocampo-Martinez, Carlos; Olaru, Sorin; Niculescu, Silviu-Iulian (Zielona Góra: Uniwersytet Zielonogórski)
MPC can effectively deal with system constraints and uncertainties with relatively low computational complexity compared with other robust MPC techniques such as min-max MPC. Set-based FDI, generally considering the worst case of uncertainties, can robustly detect and isolate actuator faults. In the proposed FTC scheme, fault detection (FD) is passive by using invariant sets, while fault isolation (FI) is active by means of MPC and tubes.
Keywords: fault detection; fault isolation; set-theoretic method; fault-tolerant control; model predictive control